Improving plant available water holding capacity of soil by solid and chemically modified biochars - Ghassemi-Golezani, Kazem; Farhangi-Abriz, Salar (Rhizosphere, 2022)
We investigated the possible effects of solid biochar and chemically modified biochars (biochar-based nanocomposites of magnesium and manganese, modified biochars with H2O2, KOH and H3PO4) on changing water retention in a silty loam texture soil. All biochar treatments were applied at a rate of 25 g biochar kg−1 soil. Results showed that application of solid biochar and especially chemically modified biochars decreased soil bulk density and saturated hydraulic conductivity, but noticeably improved water holding capacity and plant available water holding capacity in soil. The highest improvements in soil water holding capacity and plant available water holding capacity were achieved under biochar-based nanocomposites of magnesium and manganese and H3PO4 modified biochar treatments. In general, soil treatment with chemically modified biochars caused a better effect than solid biochar in increasing water availability within soil by decreasing saturated hydraulic conductivity. •Biochar and especially chemically modified biochars reduced soil bulk density.•Saturated hydraulic conductivity of soil was reduced by biochar treatments.•Water retention in soil was increased by biochar and modified biochars.•Modified biochars were more effective in increasing soil water retention.•Water availability for plants was improved by modified biochars.